Um modelo de arquitetura para o turismo ubíquo utilizando dispositivos móveis - Costa, Humberto Jorge de Moura (Universidade do Vale do Rio dos Sinos, 2013)
The use of mobile devices to use in work and leisure has grown dramatically over the years. In the tourism area, the benefits that these devices can bring are significant, considering the mobility associated with instant access and updated tourist information. One of the most relevant applications in this area are the Electronic Tour Guides (ETGs). They can provide essential information to tourists to make better use of their trip. These guides usually provide information such as where to sleep, eat and sightseeing. However, this information often are provided based on the location of the tourist, not considering resource suggestions as visiting certain attractions, according to inferences made based on information obtained from the custom preferences of the tourist and the characteristics of the environment where they are. Given the benefits that this knowledge can bring to the tourist, the aim of this work is to propose a model of software architecture, for mobile devices, that uses the concepts of ubiquitous tourism to enhance the quality of tourism experience. The proposal suggests the individual characteristics, such requirements and constraints of each tourist, together with the characteristics of the touristic environmental context. The proposed architecture, which is called UbiTour, employs several concepts of ubiquitous computing, such as context awareness, transparency to the user, location-based services, profiles, restrictions, so that the tourist can, among other activities, see what Points of Interest (POIs) are best suited to their profile in a given context. Furthermore, we proposed an ontology for ubiquitous tourism based on the proposed architecture. Besides, we conducted evaluations of UbiTour to assess the efficiency of the proposed model. We performed these evaluations using a prototype developed for iOS (iPhones and iPads). This application focused on the Caminhos de Pedra tourist itinerary, located in Bento Gonçalves, Rio Grande do Sul state, in Brazil. We applied three evaluations to this prototype: based on scenarios, focusing on the ontology, and a usability assessment. As a result, it was found that the proposed model for ubiquitous tourism helps people to have a better tourism experience.
Keywords: Turismo ubíquo; Turismo móvel; Computação ubíqua; Computação móvel; Sistemas distribuídos; Ubiquitous tourism; Mobile tourism; Ubiquitous computing; Mobile computing; Distributed systems; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação